Visualization of Water Utility Network and tracing in a web GIS application based on Open Source Technology - Chauhan, Kirtan R; Shukla, Shital H; Gaikwad, Santosh (International Journal of Computer Sciences and Engineering, 2020)
The development and management of utility networks is one of the important aspects of a city planning. The water utility network is a very important factor for any developed city. Such utility networks are complex and difficult to manage due to ever-changing data, which can be difficult to store traditionally. Storing a water utility network data in the form of spatial data with the help of GIS technology is an easy way to manage, update, and analyze such complex datasets. This paper presents how Geographical Information System has been for a web-based water utility network system (WUNS) using open source technologies for making cost-effective implementation, operation, and management of spatial information through the web. The WUNS has been developed for the Navarangpura ward, Ahmedabad. This system enables users to visualize, analyze, querying, and downloading maps of water utility network for specific requirements. The WNUS provides interactive Graphical User Interface along with basic GIS functionalities over the web for users. With using WNUS users would be able to see the accurate location of water pipeline and the overall connected assets and infrastructure also. A unique tracing functionality has been developed, showing an impact analysis to display the number of properties and population affected due to damage in a water pipeline network at a particular point/stretch. The application provides a comprehensive view of spatial and nonspatial data and can act as a decision support system for organizations, decision-makers, and city planners.